Planning for wildlife: an urban planning and design exploration to support Mexican free-tailed bats - Bradley, Dale (Kansas State University, 2015)
Anthropocentric disturbances are often the main driver behind the population decline of wildlife species. Bat species are of particular concern recently with large declines in populations worldwide. The conservation of bat species relies on knowledge about the relationship between species-specific needs and the effect urban environments have on individual species. Mexican Free-Tailed Bats (MFTBs) are listed on the IUCN Red List and play an important role in many ecosystems within the United States. Austin, Texas is home to the largest urban bat colony in the world, including MFTBs. Austin can continue to benefit from millions of dollars from ecotourism bat viewing sites and the natural control of insect populations provided by this species if urbanization does not cause a reduction in their population. The focus of this research is to develop a quantitative habitat suitability model for the MFTBs in urban areas to increase the understanding of possible MFTB habitat in the Austin Metropolitan area. A geographical information system was used to map the suitability of habitats for MFTBs in urban areas based off a typology for the needs of the species, which was created through a literature review of expert knowledge. This study will help to quantify the relationship between urban environments and the MFTBs, showing that urban areas in the Austin Metropolitan area are suitable for the species. A predictive model, like the one described here, can act as a crucial assessment and planning tool for bat conservation by helping to eliminate challenges of tracking populations or identifying bats during nocturnal activities. This model informs the proposal of planning and design policy changes in Austin, Texas to better support MFTB’s habitat needs. Adjustments to current site plans in Austin are explored understand the effect the proposed MFTB planning policies could have on current development while exploring the application of the MFTB typology at a site scale. Application of the understanding created through habitat-suitability modelling helps to visualize how current projects in Austin, Texas can better support MFTBs to create an understanding of how these policies may affect the development of urban environments.
Keywords: Landscape architecture; Planning; Mexican Free-Tailed Bat; Habitat suitability; Landscape Architecture (0390); Wildlife Conservation (0284)